(untitled) (Stamford Journal of Microbiology, 2019)
To maintain hygienic life it is important to follow the rules of sanitation. Hand sanitation is one of the most necessary parts of keeping personal hygiene. As hands are used directly for person to person contact, contact with animals, food preparation and so on, they can transmit microorganisms to and from all of these sources coming in contact. So if proper hand sanitation is maintained, the transfer of microorganisms will be decreased which can ultimately reduce the transmission of some pathogenic microorganisms to a susceptible host from own self directly or from the animals after handling them. Susceptible people getting harmful pathogenic bacteria can get sick if they find their appropriate routes of entry into them. During food preparation and taking meals, microorganisms can get entrance into the body from hands as well as microbes contaminating foods from the hands can proliferate in the foods causing spoilage and also release toxins causing food borne infection and food borne intoxication respectively. To reduce such risks people need to wash hands on routine basis especially on food processing zone it should be washed with water and soap which results in greater cleaning. People now use instant hand sanitizer after washing hands with water giving an extra protection. Sanitizers works best on hands with no visible sign of dirt. In the current study, five alcohol based hand sanitizers were selected to determine the ability of these sanitizers to decrease the loads of microorganisms from the hands of the five selected volunteers. During the study, it has been found that alcohol based instant hand sanitizer do decrease the loads of microbial flora from the hands but not in satisfactory level. Even they possessed very low effectivity against some pathogenic bacteria. These products can be used only where water is not available to decrease the loads of microbes from the hands. Stamford Journal of Microbiology, Vol.8(1) 2018: 10-14